PRE-SERVICE CHEMISTRY TEACHERS’ KNOWLEDGE, USAGE AND PERCEPTIONS OF ARTIFICIAL INTELLIGENCE IN EDUCATION - -, Harianti; Kadarohman, Asep; Anwar, Sjaeful (Universitas Negeri Surabaya, 2025)
This study investigates pre-service chemistry teachers' knowledge, use, and perceptions of AI technology integration in education. Using a survey design, data were collected from pre-service chemistry teachers enrolled in a professional teacher education program. The findings reveal varying levels of AI knowledge, with a majority having sufficient understanding but 20% demonstrating low knowledge. Social media emerged as the primary source of AI information. Participants generally felt confident using AI tools, though usage frequency varied. The study underscores the need for comprehensive AI education in teacher training programs to enhance future educators' AI literacy and integration skills. The results highlight the importance of ethical considerations and balanced AI usage to foster critical and creative thinking in educational practices. Recommendations include integrating practical AI applications, ethical considerations, and strategies for critical engagement with AI into teacher education programs to prepare pre-service teachers for future technological advancements in education.